Innovative silvofishery model in restored mangrove forests: A 10-year assessment - Suyono; Alin Fithor (Heliyon)
The novelty of this study lies in the investigations of silvofishery in 10-year-old mangrove forest in former abrasive shrimp ponds. The sedimentation depths of this mangrove forest are different from the forest area in the core mangrove forest stand zone as a fishing area. This study aims to describe the relationship between mangrove conditions, the abundance of gastropods, and mud crabs (Scylla spp.) in Pandansari Hamlet, Kaliwlingi Village, Brebes District, Brebes Regency. The different sedimentation depths of the Mangrove tourist area resulted from the different locations, which were divided into 3 stations. Station I was a muddy substrate located within the mangrove tourism area. Station II was a sandy substrate located in the mangrove forest area bordering the sea, which was only 15 m away. Finally, Station III had a muddy sand substrate in the mangrove forest near the Pemali River, which was 8 m away. For sustainability management purpose, local communities needed to be involved. Utilizing mangrove forests in combination with fishery commodities, silvofishery could protect mangrove plants while providing more yields from the fisheries. Thus, the system could increase people's income while still maintaining the sustainability of mangrove forests. Based on these findings, it could be said that mangrove forest areas were feasible to be used as the best silvofishery area in Indonesia.